Power and Charity : A Chinese Merchant Elite in Colonial Hong Kong (with a new preface) - Sinn, Elizabeth (Book collections on Project MUSE., 2003)
Through the history of a charitable institution, the Tung Wah Hospital, Elizabeth Sinn reshapes and greatly deepens our understanding of the evolving interactions between the Chinese community in Hong Kong and the colonial rulers.